2008
DOI: 10.1097/mop.0b013e328306a07c
|View full text |Cite
|
Sign up to set email alerts
|

Gynecomastia in adolescents

Abstract: Gynecomastia is frequently encountered in the primary care setting. During adolescence, male breast enlargement is most often benign and rarely represents a pathologic mechanism. Careful attention should be paid to both the breast and testicular examination. A detailed history should include an inquiry regarding the use of illicit substances, anabolic-androgenic steroids, herbal products, and medications. The impact of gynecomastia on the adolescent's mental health should be assessed. A workup for pathologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 41 publications
1
46
0
10
Order By: Relevance
“…Androgens like dihydrotestosterone, danazol, clomiphene, and aromatase inhibitors such as testolactone and anastrozole may also be effective but has limited data and less commonly used (16).…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Androgens like dihydrotestosterone, danazol, clomiphene, and aromatase inhibitors such as testolactone and anastrozole may also be effective but has limited data and less commonly used (16).…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Identified causes of gynecomastia are hypogonadism (25%), hyperprolactinemia (9%), chronic liver disease (4%), and drug induced (4%) [2]. Gynecomastia is thought to result from several mechanisms including increased androgen and leptin levels, human chorionic gonadotropin, and luteinizing hormone [3,4]. The majority of male patients with gynecomastia are asymptomatic and referred for persistently tender breasts, palpable lump, or disturbed body image [5].…”
Section: Brief Communication (Original)mentioning
confidence: 99%
“…Prevalence of asymptomatic gynecomastia is 60%-90% in neonates, 50%-60% in adolescents, and up to 70% in men age 50-69 years. [1][2][3] Trimodal distribution for asymptomatic gynecomastia is noted (neonatal, pubertal, and in elderly males). Prevalence of symptomatic gynecomastia is markedly lower.…”
Section: Incidencementioning
confidence: 99%
“…[5] Previous studies have reported that in an average out-patient clinic you may see 10 to 20 new cases of gynecomastia per year, accounting for up to 80% of all male breast referrals. [2, www.intechopen.com 3,6,7] In a recent study the referrals for specialist evaluation for gynecomastia have increased 500% since 1990's making this pathology more prevalent. [8] …”
Section: Incidencementioning
confidence: 99%